Combining physical performance and Functional Movement Screen testing to identify elite junior Australian Football athletes at risk of injury. (7th May 2020) - Jones, Stephen C.; Fuller, Joel T.; Chalmers, Samuel; Debenedictis, Thomas A.; Zacharia, Andrew; Tarca, Brett; Townsley, Alex; Milanese, Steve
Abstract : The Functional Movement Screen (FMS) and physical performance testing are often suggested to be related to sports injury risk. This study explored if the combination of FMS and physical performance testing improved identification of non‐contact injury risk over FMS testing alone in an elite junior Australian football cohort. Over a 3‐year period, 573 players completed pre‐season injury history questionnaires, FMS, physical performance testing (20‐m sprint, vertical jump, planned agility testing, and shuttle run test), and subsequent in‐season injury surveillance. Results: Neither previous injury or FMS score <14 were related to an increased risk of subsequent injury in isolation. The combination of FMS composite score ≤14 and previous injury moderately increased the risk of injury (Hazard ratio [HR] = 2.22 [1.09‐4.54]). None of the physical performance measures improved the ability to predict injuries based on FMS composite score. FMS asymmetry was only associated with injury when combined with previous injury and vertical jump performance. Players with ≥1 FMS asymmetry and history of previous injury experienced a large increase in injury risk when vertical jump was poor (HR = 4.26 [1.35‐13.42]) or good (HR = 3.17 [1.08‐9.29]). Players with a combination of a good vertical jump, no previous injury, and no FMS asymmetries were also at moderately increased risk of injury (HR = 3.41 [1.11‐10.42]). No physical performance tests improved the ability to identify non‐contact injury risk using an FMS composite score threshold. However, a U‐shaped relationship between vertical jump and injury risk was identified with both poor and good vertical jump height associated with a moderate‐large increase in non‐contact injury risk in the presence of ≥1 asymmetrical FMS sub‐test.